CONTRASTIVE ANALYSIS OF RELATIVE PRONOUNS BETWEEN ENGLISH AND KARONESE - Bonifacia EmanellabrTarigan; Elia MasaGintings (State University of Medan, 2016)
This study deals with contrastive analysis of relative pronouns between English and Karonese. The objective of this study is analyzed the differences and the similarities of relative pronouns in English and Karonese. This study used qualitative research by doing the documentary technique. The data collected by reading some references which are related to the subject matters. The data which has been collected can be qualified to solve the problem of the research. After analyzing the data, found that the similarities in both languages: Relative Pronouns in English and Karonese has the same position in a sentence, it can be: ‘after the subject or before the object’. Relative Pronouns in Ennglish and Karonese have the same form, Si can be used as subject, object, preposition and possessive for People and Things. And there are no differences of Relative Pronouns between English and Karonese as subject, object and possessive functions based on the position and form.